Two years into the Brazilian Reproducibility Initiative: reflections on conducting a large-scale replication of Brazilian biomedical science - Kleber Neves; Clarissa FD Carneiro; Ana Paula Wasilewska-Sampaio; Mariana Abreu; Bruna Valério-Gomes; Pedro B Tan; Olavo B Amaral (Memorias do Instituto Oswaldo Cruz, 2020)
Scientists have increasingly recognised that low methodological and analytical rigour combined with publish-or-perish incentives can make the published scientific literature unreliable. As a response to this, large-scale systematic replications of the literature have emerged as a way to assess the problem empirically. The Brazilian Reproducibility Initiative is one such effort, aimed at estimating the reproducibility of Brazilian biomedical research. Its goal is to perform multicentre replications of a quasi-random sample of at least 60 experiments from Brazilian articles published over a 20-year period, using a set of common laboratory methods. In this article, we describe the challenges of managing a multicentre project with collaborating teams across the country, as well as its successes and failures over the first two years. We end with a brief discussion of the Initiative’s current status and its possible future contributions after the project is concluded in 2021.